Quantum Communications and Quantum Imaging XIX (SPIE / International Society for Optical Engineering, 2021)
Proceedings of SPIE offer access to the latest innovations in research and technology and are among the most cited references in patent literature. The papers in this volume were part of the technical conference on Quantum Communications and Quantum Imaging XIX held on 1-5 August 2021, San Diego, California, United States.